Is drinking to thirst optimum? - Noakes, T. D. (Annals of Nutrition and Metabolism, 2010)
Prior to 1969, athletes were advised to avoid drinking during exercise. At least 4 subsequent events led to the adoption of a radically different approach. By 1996, all exercisers were advised to drink `as much as tolerable` in order to insure that they did not lose any weight during exercise - the `zero percent dehydration` doctrine. This advice requires that athletes drink enough to `stay ahead of thirst`. The act of drinking is a basic survival instinct that has been regulated by complex, unconscious controls ever since the first fish-like creatures moved onto land and should not require conscious adjustment. Methods: Literature survey of all studies comparing the effects of drinking to thirst (ad libitum) and drinking to prevent any weight loss during exercise - the `zero percent dehydration` doctrine. Result: No study found that drinking more than ad libitum during exercise produced any biological advantage, but it could cause exercise-associated hyponatremia. Conclusion: Drinking ad libitum appears to optimize performance and safety during exercise in many situations. The presence of thirst, not of water loss, may be the biological signal that impairs exercise performance in those who drink less than their thirst dictates during exercise.